The institutionalisation of schools and the implications for identity of experienced teachers: the case of International Baccalaureate World Schools. Issue 2 (3rd March 2020) - Bunnell, Tristan; Fertig, Michael; James, Chris
ABSTRACT: This study explored the effect that the institutionalisation forces required by the 'IB World School' authorisation process has on the identity of experienced teachers. The research analyses these institutionalising forces and the way they are carried and communicated. The institutionalising forces have a significant effect on the identity of experienced teachers. The research confirms that teacher identity is dynamic and that the identity of experienced teachers can change significantly. The institutionalisation process is powerful and appears to be coercive. However, the teachers appear to be willing participants in the institutionalisation process, and the sense of coercion the authors identified may be an unintended consequence of the process of establishing institutional legitimacy. As chains and groups of schools become more prevalent internationally, and in the English school system, the institutionalisation process in schools and the effect on the identity of teachers who work in them is likely to become more significant.